Study on the effect of wing geometry on underwater glider hydrodynamics - Nordin, K.H. (Asian Research Publishing Network, 2017)
The United States Navy have outlined an unmanned underwater vehicle master plan, which includes nine distinct capabilities for these vehicles, some of which may be suitable for underwater gliders. An underwater glider is a type of unmanned underwater vehicle that has a unique concept of propulsion using a combination of buoyancy driven engine and wings. In this paper, four different wing geometries; swept wing, swept back wing, elliptical wing and delta wing, are investigated to determine a suitable wing geometry for a given mission type. The computational fluid dynamic software, ANSYS FLUENT, was used to determine the glider hydrodynamics at different angles of attack. The delta wing has the highest drag followed by the elliptical, swept and swept back wing. Similarly, the delta wing had the highest lift; followed by the elliptical, swept and swept back wing. Underwater gliders are deemed capable of six distinct capabilities. Appropriate wing types were determined for a given mission based on three glide characteristics, which are stability/manoeuvrability, speed and endurance.